Economic reforms, liberalization, and structural change : India a nd Hungary - Sharma, R. R. (Ram Rattan), 1943-; Levai, I. (Imre) (New Delhi : Gyan Pub. House, 1997)
Majority of the papers presented in the Seventh Indo-Hungarian Round Table Conference of Economists and Policy-makers held in JNU in March 1995.
Includes bibliographical references (p. 224-226) and index.
Keywords: Free enterprise -- India -- Congresses; India -- Economic conditions -- 1947- -- Congresses; India -- Economic policy -- 1991- -- Congresses